The effect of black phosphorus additions on the structural and mechanical properties of NaXCoO2 thermoelectric - Harjinder Singh, Parveen Kaur (2024)
In recent years, condensed matter physics and materials research have focused on sodium cobaltate (NaxCoO2). Its thermoelectric qualities make it a promising component in many energy conversion applications. Sodium cobaltate was doped with different compounds to improve its thermoelectric characteristics. Conventional thermoelectric materials are unstable at high temperatures and toxic which can harm individuals and the environment. Due to the toxicity of BiTe and PbTe, this experiment uses Sodium Cobaltate, a ceramic oxide, to continue researching a stable thermoelectric material. Despite eliminating the toxicity concern of traditional thermoelectric, ceramic thermoelectric are poor in converting heat to electricity. In this work, Na0.7CoO2 with varied black phosphorus compositions (x = 0.1–1.0) is tested for enhanced performance and thermoelectric qualities. Its adjustable band gap and great carrier mobility make Black Phosphorus a semiconducting and metallic gadget. Black phosphorus, a transition metal, has a nanostructure with electrical conductivity, which increases NaxCoO2 ZT value when added. To eliminate contaminants, NaxCoO2 is produced by auto combustion. The gel samples' TG/DT analysis shows that the Na and Co nitrates decomposed in a highly exothermic single-step reaction at 250–280 °C, leaving the desired mass. XRD and FESEM indicate a well crystalline and denser sample of Na0.7CoO2 added with Black Phosphorus. Sample with x=1.0 had the maximum Vickers hardness of 428Mpa. The four-point probe method is used to investigate the thermoelectric material's electrical performance. The material has a high conductivity of 598 S∙cm-1 at 330K with x=1.0 due to the high mobility of BP, which increases electron movement and electrical conductivity.